The Analysis of Fruit Carving, an Art Qualified Culinary by The Student of Culinary Art Study Program - Kamista Putra, I Putu Raka; Witranatha, I Wayan; Grey, Kadek Rivaldo; Octa Pramesta, I Wayan Reyvas; Lingga Buana, I Putu Sila Smara; Santi Diwyarthi, Ni Desak Made; Adyatma, Prastha (Westscience Press, 2024)
This research is a qualitative research aim to analysis fruit carving, with participant observation and literature study. The research method was participant observation means researchers immerse themselves in the natural environment or social setting of the participants to do, observe and document behaviors, interactions, and cultural practices. The exploration of fruit carving through participatory observation in qualitative research unveils a unique blend of artistic expression, cultural tradition, health awareness, sustainability, and educational significance. This amalgamation renders fruit carving a multifaceted and enriching area of study, offering novel insights into its diverse dimensions. This approach is particularly useful for studying social dynamics and cultural phenomena. The result was fruit carving's uniques lie in its strength, such as widespread popularity, art and cultural heritage. Fruit carving weaknesses include price instability and dependency on high-quality fruit carving. Opportunities for business growth include creating variations and marketing to culinary tourists, while threats include intense competition and uncertainty in raw material supply. Overall, leveraging its strengths while addressing weaknesses and seizing opportunities will be crucial for the success of fruit carving existence in the future.